Ganito kami noon, paano kayo ngayon? - Romero, Eddie; Iglesias, Roy; De Leon, Christopher; Garcia, Eddie; Salcedo, Leopoldo; Belleza, Dranreb; Diaz, Gloria
A comedy about Kulas, a naive peasant who is entrusted to care for a Spanish friar's son. He wanders through the Philippine Revolution of 1896-98, witnessing the fall of the Spanish and the arrival of the Americans, while struggling to define what a Filipino is.